(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract: Phytochemicals, bioactive compounds derived from plants, have emerged as potential enhancers of chemotherapy, offering novel strategies to improve cancer treatment outcomes. This paper reviews the evidence on the role of phytochemicals in augmenting chemotherapy by addressing mechanisms such as drug resistance modulation, side effect reduction, and synergistic interactions with chemotherapeutic agents. Phytochemicals like curcumin, resveratrol, and green tea polyphenols have shown promise in preclinical studies for their ability to sensitize cancer cells to chemotherapy, reduce oxidative stress-related side effects, and enhance drug efficacy. These promising findings, clinical evidence remains variable due to challenges such as individual response differences and bioavailability issues. The paper highlights the need for further research to address these challenges, optimize phytochemical formulations, and establish clear guidelines for their use in clinical settings. Integrating phytochemicals into cancer treatment regimens could potentially lead to more effective therapies and improved patient quality of life. This review aims to provide a comprehensive understanding of the current evidence and suggest future directions for research in this promising area.